Investigation of Amphibian Mortality Events in Wildlife Reveals an On-Going Ranavirus Epidemic in the North of the Netherlands. - Jolianne M Rijks; Bernardo Saucedo; Annemarieke Spitzen-van der Sluijs; Gavin S Wilkie; Alphons J A M van Asten; Jan van den Broek; Roschong Boonyarittichaikij; Marisca Stege; Fleur van der Sterren; An Martel; Frank Pasmans; Joseph Hughes; et al. (PLoS ONE)
In the four years following the first detection of ranavirus (genus Ranavirus, family Iridoviridae) infection in Dutch wildlife in 2010, amphibian mortality events were investigated nationwide to detect, characterize and map ranaviruses in amphibians over time, and to establish the affected host species and the clinico-pathological presentation of the disease in these hosts. The ultimate goal was to obtain more insight into ranavirus disease emergence and ecological risk. In total 155 dead amphibians from 52 sites were submitted between 2011 and 2014, and examined using histopathology, immunohistochemistry, virus isolation and molecular genetic characterization. Ranavirus-associated amphibian mortality events occurred at 18 sites (35%), initially only in proximity of the 2010 index site. Specimens belonging to approximately half of the native amphibian species were infected, including the threatened Pelobates fuscus (spadefoot toad). Clustered massive outbreaks involving dead adult specimens and ranavirus genomic identity indicated that one common midwife toad virus (CMTV)-like ranavirus strain is emerging in provinces in the north of the Netherlands. Modelling based on the spatiotemporal pattern of spread showed a high probability that this emerging virus will continue to be detected at new sites (the discrete reproductive power of this outbreak is 0.35). Phylogenetically distinct CMTV-like ranaviruses were found in the south of the Netherlands more recently. In addition to showing that CMTV-like ranaviruses threaten wild amphibian populations not only in Spain but also in the Netherlands, the current spread and risk of establishment reiterate that understanding the underlying causes of CMTV-like ranavirus emergence requires international attention.